2003
DOI: 10.1029/2002jb001880
|View full text |Cite
|
Sign up to set email alerts
|

Deep structure of the Baikal rift zone revealed by joint inversion of gravity and seismology

Abstract: [1] The question of plate boundary forces and deep versus shallow asthenospheric uplift has long been debated in intracontinental rift areas, particularly in the Baikal rift zone, Asia, which is colder than other continental rifts. As previous gravity and teleseismic studies support the dominance of opposing mechanisms in the Baikal rift, we reconsidered both data sets and jointly inverted them. This more effective approach brings insight into location of the perturbing bodies related to the extension in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 67 publications
(114 reference statements)
3
68
0
7
Order By: Relevance
“…The observed variation of the MTZ thickness is consistent with seismic tomography results. Although most seismic tomography studies [e.g., Achauer and Masson , 2002; Gao et al , 1994b, 2003; Tiberi et al , 2003] revealed low‐velocity regions in the upper mantle beneath the rift, there still lacks strong evidence for such anomalies extending to the MTZ. On the contrary, a recent seismic tomography study [ Zhao et al , 2006] suggested a high‐velocity region with a magnitude of 1–2% in the MTZ beneath the rift.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed variation of the MTZ thickness is consistent with seismic tomography results. Although most seismic tomography studies [e.g., Achauer and Masson , 2002; Gao et al , 1994b, 2003; Tiberi et al , 2003] revealed low‐velocity regions in the upper mantle beneath the rift, there still lacks strong evidence for such anomalies extending to the MTZ. On the contrary, a recent seismic tomography study [ Zhao et al , 2006] suggested a high‐velocity region with a magnitude of 1–2% in the MTZ beneath the rift.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the use of a standard earth model in calculating the moveout times and the location of the ray‐piercing points has insignificant effects on the main conclusions of the study, i.e., the BRZ is underlain by a thickened MTZ, as most clearly suggested by the uplift of the d 410. In addition, the currently available velocity models for the study area [e.g., Zhao et al , 2006; Gao et al , 2003; Tiberi et al , 2003; Achauer and Masson , 2002; Petit et al , 1998] show considerable inconsistencies with each other. This will make it difficult technically to use any one of them for the correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Краевой шов Сибирской платформы блокирует распространение рифтогенных процес-сов к западу, а его изогнутая геометрия влияет на кинематические параметры существующих раз-рывных нарушений, активизированных в позднем кайнозое под воздействием СЗ-ЮВ растяжения. Независимо от механизма формирования Байкаль-ской рифтовой зоны, который объясняют подъ-емом аномальной мантии и/или воздействием на подошву литосферы астеносферного потока в ЮВ направлении, а также сжатием в СВ направлении, связанным с Индо-Евразийской коллизией [Molnar, Tapponnier, 1975;Zorin, 1981;Petit et al, 1998;Logachev et al, 2000;Zorin et al, 2003;Tiberi et al, 2003;Lebedev et al, 2006;Kulakov, 2008;Petit, Déverchère, 2006;San'kov et al, 2011;Sankov et al, 2015;и мн. др.…”
Section: согласованность результатов с общепринятыми научными взглядамиunclassified
“…To reduce this nonuniqueness, recent approaches have been developed in using multiple geophysical data sets especially when their sensitivity maps are complementary to each other (e.g., Gallardo-Delgado et al, 2003;Tiberi et al, 2003;Buland and Kolbjømsen, 2012). Various structural approaches have been developed for the joint inversion of geophysical data (e.g., Haber and Oldenburg, 1997;Zhang and Morgan, 1997).…”
Section: Introductionmentioning
confidence: 99%